Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy320
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder from a Developmental Psychopathology Perspective: Focusing on Phenomenology, Etiology, and Neurobiology

Abstract: The purpose of this chapter is to consider how a developmental psychopathology perspective can advance our understanding of bipolar disorder. In this chapter we start by discussing the phenomenology of the disorder. As this is a field in which scientific controversies abound, this section begins by placing bipolar disorder in a historical context. We consider the origins of current clinical diagnostic approaches and evaluate newly emerging empirical approaches that utilize dimensions of symptoms, behaviors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 365 publications
0
4
0
Order By: Relevance
“…Finally, it is possible that IQ functioning is sexually dimorphic in BDO [ 82 ]. Most of the studies that found enhanced IQ in those who went on to develop BD used conscript samples composed of males (e.g., [ 5 , 19 , 25 ]; an exception is a cohort study [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that IQ functioning is sexually dimorphic in BDO [ 82 ]. Most of the studies that found enhanced IQ in those who went on to develop BD used conscript samples composed of males (e.g., [ 5 , 19 , 25 ]; an exception is a cohort study [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is still considerable debate regarding the relationship between DSM classifications and genetic homogeneity, it is likely that homogeneity gained by studying the early-onset phenotype will be negated by including the full range of BDs, especially when there is evidence of substantial genetic heterogeneity among the bipolar disorders (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013). This discussion about diagnostic inclusion criteria has been especially salient when the focus is on a population who is continuing to undergo development, leading to ongoing, lively debates in the field about what features of BD are represented early in development, how these characteristics change across development, and methods of altering the probabilistic risk trajectories (Klimes-Dougan et al, in press). …”
Section: Discussionmentioning
confidence: 99%
“…Although we required that DSM criteria for BD be met (either DSM-III or DSM-IV), we did not place any restrictions on the types of BD included such as bipolar I disorder (BDI) or bipolar II disorder (BDII). Historically a range of criteria have been applied children and adolescent BD diagnosis (as reviewed by Klimes-Dougan et al, in press), but the genetic studies reviewed here typically applied a “narrow” DSM definition of BD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation